2018
DOI: 10.1111/cas.13881
|View full text |Cite
|
Sign up to set email alerts
|

20(S)‐ginsenoside‐Rg3 reverses temozolomide resistance and restrains epithelial‐mesenchymal transition progression in glioblastoma

Abstract: Glioblastoma multiforme (GBM) is one of the most malignant human intracranial tumors. Temozolomide (TMZ) is the primary alkylating agent for GBM patients. However, many GBM patients are resistant to TMZ. Therefore, patients with GBM urgently need more effective therapeutic options. 20(S)‐ginsenoside‐Rg3 (20(S)‐Rg3) is a natural chemical with anti‐tumor effects, but at present there is little understanding of its functional mechanism. Several research reports have demonstrated that O6‐methylguanine DNA‐methyltr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(32 citation statements)
references
References 47 publications
(81 reference statements)
1
31
0
Order By: Relevance
“…However, the relatively quick development of chemoresistance to this compound limits the efficacy of this therapeutic strategy [36]. Currently, a number of different and distinct mechanisms of TMZ resistance have been identified by researchers, including mechanisms that are dependent upon DNA O 6 -methylguanine methyltransferase (MGMT), DNA mismatch repair (MMR), base excision repair (BER), and the ATP-binding cassette (ABC) protein family [37][38][39][40]. Given these diverse mechanisms and the key role of TMZ in treating GBM, it is clear that more research needs to be performed to determine how TMZ resistance develops and what strategies are effective in increasing the sensitivity of TMZ-R cell lines to chemotherapeutic treatments.…”
Section: Discussionmentioning
confidence: 99%
“…However, the relatively quick development of chemoresistance to this compound limits the efficacy of this therapeutic strategy [36]. Currently, a number of different and distinct mechanisms of TMZ resistance have been identified by researchers, including mechanisms that are dependent upon DNA O 6 -methylguanine methyltransferase (MGMT), DNA mismatch repair (MMR), base excision repair (BER), and the ATP-binding cassette (ABC) protein family [37][38][39][40]. Given these diverse mechanisms and the key role of TMZ in treating GBM, it is clear that more research needs to be performed to determine how TMZ resistance develops and what strategies are effective in increasing the sensitivity of TMZ-R cell lines to chemotherapeutic treatments.…”
Section: Discussionmentioning
confidence: 99%
“…Ginsenoside is an important active ingredient of ginseng and it has been used as an anticancer Chinese medicine in the treatment of malignant tumors such as melanoma and prostate cancer . Ginsenoside Rg3, the main component of Ginsenoside, has been shown to inhibit tumor progression and chemoresistance, for example, Ginsenoside Rg3 attenuates temozolomide resistance and epithelial‐mesenchymal transition (EMT) progression in glioblastoma; Ginsenoside Rg3 inhibits prostate cancer cell proliferation through inducing cell cycle arrest . Recent studies showed that Ginsenoside Rg3 could target CSCs in colorectal cancer and Ginsenoside Rg3 could enhance cisplatin sensitivity via blocking EMT process and stemness in lung cancer cells .…”
Section: Introductionmentioning
confidence: 99%
“…Aberrant functions of miRNAs may impede the interactions between miRNAs and their mRNA targets, a few examples of which are miRNA-210-3p and the multidrug efflux transporter ABCC5 (also known as MRP5; Amponsah et al, 2017); miRNA-101 and DNA-dependent protein kinases (Hu et al, 2017); miRNA-125a and the pro-apoptotic protein A20 (Yao et al, 2016); miR-145 and the ribosomal protein S6 kinase p70S6K1 (Lin et al, 2016); miRNA-181b and the cylindromatosis protein CYDL (Takiuchi et al, 2013); miRNA-144-3p and the AT-rich interactive domain 1A protein ARD1A (Xiao et al, 2017); and miRNA-199a-5p and miRNA-375 with the PH domain and leucine-rich repeat protein phosphatase 1 PHLPP1 (Mussnich et al, 2015). An impaired interaction between miRNA and its mRNA target unescapably results in tumor cell resistance, since these targets are elements of key cellular signaling cascades such as NF-κβ, AKT, and JAK2/STAT3, which control apoptosis, cell cycle progression, DNA repair, RNA editing, and nucleotide synthesis (Wu et al, 2018; Chen et al, 2019). Based on these data, investigators have attempted to use combinations of miRNA-based therapeutics in conjunction with chemotherapeutics to overcome the development of resistance and to increase the efficacy of treatment.…”
Section: Combination Of Mirna-based Therapeutics and Chemotherapy Tomentioning
confidence: 99%